Using visual media for improving students’ vocabulary achievement - Viqi Ardaniah, Ni Wayan Sartini, Sheila Wijayanti, (Opción, 2019)
This study aims at discussing the method for improving the junior high school students’ vocabulary achievement by using visual media, namely Pop-up Pictures via comparative qualitative research methods. The result of the observation shows an improvement in the percentage of the students’ participation from 86% to 88.9%. In conclusion, English teachers are suggested to use Pop-up Pictures as alternative media for teaching vocabulary to improve the students’ vocabulary achievement and the students’ participation.